Humiliation among students. Processes of superiorization and inferiorization in young people of high schools - Carina Viviana Kaplan; Agustina Mutchinick (Universidade Federal de Santa Catarina, 2019)
This work presents an investigation that analyzed the humiliations among students of secondary schools. In particular, this paper addresses two of the dimensions analyzed in the study: the symbolic effects of the humiliations on the school and social experience of those who are humiliated and the reasons given by the students interviewed why young people humiliate their classmates. A qualitative research strategy was adopted. In-depth interviews were conducted with young people of two schools in the province of Buenos Aires (Argentina). From the results obtained, we can affirm that humiliation is constituted as a social relation between individuals or groups in which processes of superiorization and inferiorization unfold where those who humiliate pretend be better than those who are humiliated and make them feel the contempt of which they are recipients. These modes of linking have a desubjective but also subjective character that becomes central in the identity processes that young people develop in the school space.